On Prevention and Treatment of Warm Fog on Highways with the Help of Spatially Inhomogeneous Electric Field - Alekseeva, Alexandra; Davidov, Vladimir; Paley, Aleksey; Pisanko, Yuri; Schelkalin, Alexei; Zinkina, Marina (Prevention and Treatment of Natural Disasters, 2025)
A few potential techniques to prevent and disperse warm fogs on highways are discussed. Among these are those based on a net as it is, and also on the combination of net and high voltage electrodes for corona discharge. As a perspective technique, presented is the use of the spatially inhomogeneous electric field for fog dispersion. Our ultimate goal is to propose the fog dispersion technical means based on the use of such a field. In this technique, the electric force acts on droplets directly (via droplet’s dipole moment but not via droplet’s electric charge) without the intermediate stage of air ionization by corona discharge and droplet’s charging. The advantage is that the electric field energy is directly exploited to remove fog droplets from controlled space; there is no energy waste to generate the corona discharge. The described techniques are patented in Russia. On the first step, our methodology includes laboratory experiments. In our laboratory‑scale plant, we explore the use of spatially inhomogeneous electric field as a potential technique for warm fog dispersion. In the experiments, the fog, naturally dispersing during half an hour, becomes much more transparent 10 s after the electrode (40 mm in diameter situated in the chamber center) was supplied with the high voltage of 30 kV. The fog is completely dispersed 50 s after the high voltage was turned on. These first results look promising for future efforts to create technical means of fog dispersion via inhomogeneous electric field.